LANDSLIDE ZONATION MAPPING AND VULNERABILITY ASSESSMENT OF SATARA AND RAIGAD DISTRICT - M M, Kumthekar; Patil, Chetan S; M.B., Kumthekar; Kambal, Rajguru Suhas (Ra'e Ga: o Espaço Geográfico em Análise, 2024)
Geographic information (GIS) systems are the influential tools which facilitate the retrieval, collection, analysis, storage and the exhibition of spatial evidence. Remote sensing (RS) is generally defined as the procedure for acquiring evidence on the surface of the earth deprived of corporeal interaction to analyse the vulnerability of the landlside. Analytical Hierarchy (AHP) Process is executed for the analysis. GIS and RS has modernized the regulating measures of the regular hazards. In this contemporary research, Landslide Zonation Mapping and Vulnerability Assessment of the Satara and Raigad District is briefed. The research has investigated Latitude, longitude, soil, texture and the categories of landslides on the study region of Patan and Mahad. Also, the site visit was completed, sample of the soil was collected, DEM were reclassified, digital elevation (DEM) model formation executed, vulnerable susceptibility zones are pin pointed and finally the model is prepared. Rainfall analysis is executed since most of the landslides are caused because of the rainfall. Slope, aspect, flow direction of the study area, and finally the land use and land cover (LULC) mapping are conducted. Based on the research it is concluded that vulnerability of the locations is medium or high. Region with intermediate slopes, decreased rainfall, forest cover on the opposite side it is named as the least vulnerable regions of Patan. In Mahad, 059 % of the region is in higher risk, whereas the 49.336% is in the intermediate risk, then 41.462% is in minimum risk and 9% comes under the category of no risk.